Plasmon-assisted click chemistry at low temperature: an inverse temperature effect on the reaction rate - Guselnikova, Olga; Váňa, Jiří; Phuong, Linh Trinh; Panov, Illia; Rulíšek, Lubomír; Trelin, Andrii; Postnikov, Pavel; Švorčík, Václav; Andris, Erik; Lyutakov, Oleksiy (Chemical science, 2021)
Plasmon assistance promotes a range of chemical transformations by decreasing their activation energies. In a common case, thermal and plasmon assistance work synergistically: higher temperature results in higher plasmon-enhanced catalysis efficiency. Herein, we report an unexpected tenfold increase in the reaction efficiency of surface plasmon-assisted Huisgen dipolar azide-alkyne cycloaddition (AAC) when the reaction mixture is cooled from room temperature to -35 °C. We attribute the observed increase in the reaction efficiency to complete plasmon-induced annihilation of the reaction barrier, prolongation of plasmon lifetime, and decreased relaxation of plasmon-excited-states under cooling. Furthermore, control quenching experiments supported by theoretical calculations indicate that plasmon-mediated substrate excitation to an electronic triplet state may play the key role in plasmon-assisted chemical transformation. Last but not least, we demonstrated the possible applicability of plasmon assistance to biological systems by AAC coupling of biotin to gold nanoparticles performed at -35 °C.